Low Oxygen Concentration Reduces Neisseria gonorrhoeae Susceptibility to Resazurin - Justin Rice; Jordan Gibson; Emily Young; Kendall Souder; Kailee Cunningham; Deanna M. Schmitt (MDPI AG, 2024)
Neisseria gonorrhoeae has developed resistance to every antibiotic currently approved for the treatment of gonorrhea, prompting the development of new therapies. The phenoxazine dye resazurin exhibits robust antimicrobial activity against N. gonorrhoeae in vitro but fails to limit vaginal colonization by N. gonorrhoeae in a mouse model. The lack of in vivo efficacy may be due to oxygen limitation as in vitro susceptibility assays with resazurin are conducted under atmospheric oxygen while a microaerophilic environment is present in the vagina. Here, we utilized broth microdilution assays to determine the susceptibility of N. gonorrhoeae to resazurin under low and atmospheric oxygen conditions. The minimal inhibitory concentration of resazurin for multiple N. gonorrhoeae clinical isolates was significantly higher under low oxygen. This effect was specific to resazurin as N. gonorrhoeae was equally susceptible to other antibiotics under low and atmospheric oxygen conditions. The reduced susceptibility of N. gonorrhoeae to resazurin under low oxygen was largely attributed to reduced oxidative stress, as the addition of antioxidants under atmospheric oxygen mimicked the reduced susceptibility to resazurin observed under low oxygen. Together, these data suggest oxygen concentration is an important factor to consider when evaluating the efficacy of new antibiotics against N. gonorrhoeae in vitro.